2015
DOI: 10.1097/mpg.0000000000000888
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Bolus or Semicontinuous Feeding for Preterm Infants?

Abstract: Bolus and continuous feeding are equally suitable feeding strategies for preterm neonates. BOL feeding, however, may be preferable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
(34 reference statements)
3
36
0
Order By: Relevance
“…Our enteral and parenteral nutrition protocol has been described previously20. If expressed breast milk was insufficiently available, preterm formula was supplemented (Nenatal Start ® , Nutricia, Zoetermeer, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…Our enteral and parenteral nutrition protocol has been described previously20. If expressed breast milk was insufficiently available, preterm formula was supplemented (Nenatal Start ® , Nutricia, Zoetermeer, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…The continuous feedings were associated with more total apneic periods, more apneic periods lasting >20 s and more hypoxic episodes when compared to bolus feedings. In a randomized trial of intermittent bolus or semicontinuous nasogastric tube feedings in 246 low birth weight preterm infants, Rövekamp-Abels et al found significantly lower mean daily gastric residual volumes in the bolus group (69). However, gastroesophageal reflux, respiratory complications, and time to full oral feeds were not assessed as outcomes in this population.…”
Section: Management Of Oropharyngeal Dysphagia-associated Feeding Difmentioning
confidence: 99%
“…After day 3, the intervention ended and thereafter the attending physician followed the local standardized protocol . The enteral nutrition (EN) protocol included minimal enteral feeding at day 1 and a daily gradual increment of approximately 20 mL/(kg·d) of enteral bolus feeding from day 2 or 3 onward until 150–180 mL/(kg·d) was reached.…”
Section: Methodsmentioning
confidence: 99%